Keseimbangan Energi Biomassa Gas Metan PLTGU 20 MW - Istianto Budhi Rahardja (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
The energy balance in the composition of methane gas is the result of mass changes from a gaseous mass to another mass (calorie and other mass) from the burning of methane gas in the Gas-Steam Power Plant system. The result of the combustion of methane will produce heat and waste products of combustion such as carbon dioxide, moisture, oxygen, and nitrogen. The calorie produced is used in the power plant system, while the waste of the result of combustion are released into the environment. The balance of energy in the combustion of methane gas have calorific, enthalpy and entropy values. The methane gas that will be changing from the gas into heat energy and combustion results done by the provision of a high temperature so that the methane exceeds the threshold value. The methane gas that goes into the power plant system will be changed by the heat energy that has been formed to drive a gas turbine and heat water in the boiler to drive a steam turbine. The result of the combustion of methane gas is used to drive the power plant that had been planned. The combustion of methane gas with an average composition of methane 22.8 Kg/s and oxygen at 6.7 Kg/s would produce a balance in the oven for 22.8 CO2; 45.6 H2O; – 38.9 O2; 25.192 N2. The calorific value and X destroyed formed amounted to 1,156,425.1 KJ/s; 3,829,334.1328 MJ/Kmol CH4.